1991
DOI: 10.1007/bf01249108
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of testicular regression by 12-hr temporal relationship of serotonergic and dopaminergic activity in Indian Palm Squirrel,Funambulus pennanti

Abstract: Specific temporal relationship (12-hr) of serotonin and dopamine activity was induced by precursor drugs (5-HTP and L-DOPA) in Indian Palm Squirrel Funambulus pennanti during testicular regression phase. This treatment established breeding condition unlike control, which experienced complete atrophy of testes and accessory sex organs. It is obvious that seasonal testicular regression of Indian Palm Squirrel can be eliminated by 12 hr relation of 5-HTP and L-DOPA, which is not a pharmacological effect but actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…This suggests a stimulatory effect of this relationship on the rate of reproduction/fertility. However, testis growth/volume and spermatogenic activity in 12-h mice (unlike the plasma testosterone level and the sperm index) were not signifi cantly different from the controls, in contrast to previous reports on various other species (Wilson and Meier 1989;Chaturvedi and Bhatt 1990;Chaturvedi and Prasad 1991;Jaiwal and Chaturvedi 1991;Phillips and Chaturvedi 1995;. By the end of the study, the control mice attained nearly full gonadal development; but, a stimulatory effect of the 12-h phase relation on all the parameters of testicular function was not evident, in spite of a signifi cantly increased degree of gonadal activity as compared with the controls.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This suggests a stimulatory effect of this relationship on the rate of reproduction/fertility. However, testis growth/volume and spermatogenic activity in 12-h mice (unlike the plasma testosterone level and the sperm index) were not signifi cantly different from the controls, in contrast to previous reports on various other species (Wilson and Meier 1989;Chaturvedi and Bhatt 1990;Chaturvedi and Prasad 1991;Jaiwal and Chaturvedi 1991;Phillips and Chaturvedi 1995;. By the end of the study, the control mice attained nearly full gonadal development; but, a stimulatory effect of the 12-h phase relation on all the parameters of testicular function was not evident, in spite of a signifi cantly increased degree of gonadal activity as compared with the controls.…”
Section: Discussioncontrasting
confidence: 85%
“…Both testes were excised and weighed. The testicular volume was calculated using Bissonett's formula 4/3πab 2 (a = ½ the long axis; b = ½ the short axis) (Jaiwal and Chaturvedi 1991;Chaturvedi et al 1993). …”
Section: Experimental Designmentioning
confidence: 99%
“…Second study in this series reported that L-DOPA injected 12 hr after 5-HTP may even induce redevelopment of gonad up to full breeding condition when given in sexually quiescent phase of annual cycle (Jaiwal and Chaturvedi, 1991). Next experiment in this series (present study) was designed to study the effect of L-DOPA injected 8 hr after 5-HTP (8 hr relationship, gonadoinhibitory) in this species during breeding phase.…”
Section: Introductionmentioning
confidence: 94%
“…Twenty-four days after the last injection, when the mice were 58 days old, they were anesthetized and treated as described for study I. The length and width of the left testis was measured in situ with dial calipers, and the testicular volume was calculated using Bissonett’s formula (4/3) π ab 2 ( a = 1/2 of the long axis; b = 1/2 of the short axis) [8,9]. Histological sections of the testis were viewed under a microscope (Axioskop 2 Plus; Carl Zeiss, Oberkochen, Germany), and images were captured with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, if these drugs are injected 8 h apart (8- hour relation), this may lead to gonadal suppression/non-breeding conditions, while other relations (0, 4, 16 and 20 h) have been found to be ineffective. In the Indian palm squirrel, Funambulus pennantii , the 12-hour phase relation of serotonergic and dopaminergic oscillations not only extends the breeding season, but may also eliminate annual reproductive regression [8]. On the other hand, in this subtropical mammalian species, an 8-hour phase relation stimulates non-breeding conditions out of season [9].…”
Section: Introductionmentioning
confidence: 99%